2012
DOI: 10.2460/ajvr.73.11.1807
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intraocular pressure in conscious Hermann's tortoises (Testudo hermanni) by means of rebound tonometry

Abstract: Rebound tonometry was a practical and rapid means of determining IOP in small- to medium-sized tortoises that required minimal manual restraint of the animals. Establishing IOP values in healthy Hermann's tortoises will provide a reference frame for use during complete ophthalmic examinations, thus allowing clinicians to diagnose a broader spectrum of ocular pathological conditions in tortoises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 62 publications
2
14
1
Order By: Relevance
“…Intraocular pressure in wild animals has previously been evaluated using indentation tonometry and applanation tonometry and rebound tonometry . Few studies about IOP in reptiles, especially testudine species, were reported in the literature . Specifically, in red‐eared slider turtles, there is only one study reporting this parameter .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intraocular pressure in wild animals has previously been evaluated using indentation tonometry and applanation tonometry and rebound tonometry . Few studies about IOP in reptiles, especially testudine species, were reported in the literature . Specifically, in red‐eared slider turtles, there is only one study reporting this parameter .…”
Section: Discussionmentioning
confidence: 99%
“…The available literature focuses on ocular diseases, pathophysiologic mechanisms and clinical treatments . Some available studies with reptile species also report normal ophthalmic parameters and selected clinical tests . Normal values for rebound tonometry and tear production have been reported for red‐eared slider turtles.…”
Section: Introductionmentioning
confidence: 99%
“…The other needle was connected to a pressure transducer (NL108T2 Disposable Physiological Pressure Transducer, Warner Instruments, Hamden, CT) and continuous physiologic recorder (Dash â 4000 Pro, GE Healthcare, Milwaukee, WI) allowing IOP to be verified and continuously recorded. Triplicate TonoLab â followed by TonoVet â readings were acquired as described below, by the same observer (CD) at 5,10,15,20,25,30,35,40,50,60,70, and 80 mmHg for each eye.…”
Section: Comparison Of Rebound Tonometry With Direct Manometry Ex Vivomentioning
confidence: 99%
“…[11, 12, 14, 19] Although TonoVet® rebound tonometry was recently described in tortoises,[10] the accuracy of these readings, when compared to true IOP as measured by a manometer and the effects of manual and chemical restraint on IOP, have not been evaluated in any reptile species. The purpose of this study was to evaluate the ability of two rebound tonometers, the TonoVet® and TonoLab®, to estimate IOP in adult red-eared slider turtles using different methods of manual and chemical restraint and to compare IOP estimates obtained with these two devices to a manometer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation